Recent advances in intestinal smooth muscle research: from muscle strips and single cells, via ICC networks to whole organ physiology and assessment of human gut motor dysfunction - Huizinga, Jan D. (Journal of Smooth Muscle Research, 2019)
Gastrointestinal smooth muscle research has evolved from studies on muscle strips to spatiotemporal mapping of whole organ motor and electrical activities. Decades of research on single muscle cells and small sections of isolated musculature from animal models has given us the groundwork for interpretation of human in vivo studies. Human gut motility studies have dramatically improved by high-resolution manometry and high-resolution electrophysiology. The details that emerge from spatiotemporal mapping of high-resolution data are now of such quality that hypotheses can be generated as to the physiology (in healthy subjects) and pathophysiology (in patients) of gastrointestinal (dys) motility. Such interpretation demands understanding of the musculature as a super-network of excitable cells (neurons, smooth muscle cells, other accessory cells) and oscillatory cells (the pacemaker interstitial cells of Cajal), for which mathematical modeling becomes essential. The developing deeper understanding of gastrointestinal motility will bring us soon to a level of precision in diagnosis of dysfunction that is far beyond what is currently available.